The Assisting Publication of an Anthology Entitled Tak Selalu Hitam Putih, Kisah di Balik Pengabdian - Utami, Tresiana Sari Diah; Triwidayati, Katarina Retno (CV. Creative Tugu Pena, 2022)
This service is entitled Assisting The Publication of an Anthology Entitled Tak Selalu Hitam Putih, Kisah di Balik Pengabdian. The target and outcome of this activity are HIMPAUDI educators throughout Central Java who will publish an anthology containing articles written by educators. After the activity, it is hoped that the educators will be able to publish the anthology. The method used in this activity is a question and answer method, discussion, and assignment. Activities are carried out online. The first and last meetings were held via the Zoom application and four meetings were held by discussion via WAG. The results of the activity were in the form of 52 articles regarding participants' experiences as administrators or members of Himpaudi. In addition, the articles produced are in the form of participants' experiences as educators. An anthology book entitled Not Always Black and White, The Story Behind Devotion. The satisfaction questionnaire showed that 83.7% of the participants had received the training material provided, 22.4% had written articles, 100% of the participants felt this activity was important, the material presented by the resource person was 90% complete, 89.8% of the participants felt the material presented by the resource person was understood, 98% participants intend to write articles after participating in the PkM conducted by the UKMC team, and 98% of participants are willing to take part again in similar training Keywords: Assisting Publication, Anthology, Analyzing Anthology